Comparison between laparoscopic and open partial nephrectomy: Surgical, oncologic, and functional outcomes - Zhuo Liu; Ping Wang; Dan Xia; Yang-Feng Lou; Hua-Feng Pan; Shuo Wang (Kaohsiung Journal of Medical Sciences, 2013)
The surgical, oncologic, and functional outcomes were retrospectively compared of laparoscopic partial nephrectomy (LPN) and open partial nephrectomy (OPN) for the treatment of renal masses. Between January 2006 and November 2011, 115 LPNs and 97 OPNs were performed. The patients’ demographics were matched. Their intraoperative and postoperative data, oncologic and renal function outcomes were compared. Surgical time, renal arterial occlusion time, estimated blood loss, and postoperative hospitalization days were shorter in the LPN group (p < 0.01). The total complications were comparable; however, LPN had a higher intraoperative complication due to 12 subcutaneous emphysemas. The LPN group was followed up with a mean time of 29.3 ± 14.4 months and the OPN group with a mean time of 31.2 ± 12.6 months. All patients survived and no distant relapse or metastasis were observed. Kaplan–Meier estimates of 60-month local recurrence-free survival were comparable with 92.4% after LPN and 93.8% after OPN, respectively (p = 0.57). The reduction of glomerular filtration rate was more obvious after LPN at the 3-month follow-up (p < 0.01), but similar between the two groups at the 30.2-month follow-up. LPN provides similar results in oncologic and functional outcomes when compared to OPN. Long-term observations are still required to the oncologic and function outcomes.